Trends in International Mathematics and Science Study (TIMSS): A Comparative Analysis of Mathematics Achievement - Rubio, Marilyn T.; Mensah, John; Sokpe, Benjamin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study investigates global trends in mathematics education using TIMSS data to understand factors influencing student achievement. Methodology: Quantitative analysis of TIMSS datasets from the latest cycles was conducted using statistical tools such as SPSS and R for trend analysis, regression models, and comparative performance evaluations. Main Findings: Socioeconomic factors, teacher qualification, and curricular alignment were strongly associated with variations in student performance across countries. Novelty/Originality of this study: The study offers a detailed comparative analysis of the latest TIMSS results, emphasizing underrepresented countries, thereby contributing to strategies for improving global mathematics education.